Influence of Elevated Temperatures on Compressive Strength of Concrete Containing Laterite Aggregate - Khairunisa, Muthusamy; Sabrina, Emmanuel; Norul Wahida, Kamaruzaman (2014)
The present investigation looks into the effect of laterite aggregate as partial coarse aggregate replacement towards performance of concrete upon exposure to elevated temperature. Two mixes namely plain concrete with 100% granite aggregate and laterite concrete with 10% laterite stone as partial coarse aggregate replacement were prepared in form of cubes. All the specimens were water cured for 28 days before exposed to various level of high temperature. After that, it is left to cool down to room temperature by applying air cooling system. Behaviour of concrete upon exposure to high temperature has been evaluated through determination of mass loss and compressive strength reduction. The percentage of mass loss and compressive strength ratio pattern displayed by laterite concrete is similar to plain concrete. However, the variation in the percentage of mass loss and strength ratio of laterite concrete is governed by the different physical properties of laterite aggregate in comparison to granite aggregate. The temperature between 300 oC and 800 oC may be regarded as critical to the strength loss of laterite concrete.